Willingness of Ethiopian Population to Receive COVID-19 Vaccine - Belsti, Yitayeh; Gela, Yibeltal Yismaw; Akalu, Yonas; Dagnew, Baye; Getnet, Mihret; Abdu Seid, Mohammed; Diress, Mengistie; Yeshaw, Yigizie; Fekadu, Sofonias Addis (Journal of multidisciplinary healthcare, 2021)
Despite efforts to decrease the burden, vaccine reluctance is increasing worldwide and hindering efforts to control the spread of COVID-19. Therefore, understanding the willingness of a community to receive a COVID-19 vaccine will help to develop and implement effective means of promoting COVID-19 vaccine uptake. This study was aimed to assess the willingness of the Ethiopian population to receive the COVID-19 vaccine and its determinant factors. E-survey was conducted from February 2021 to March 2021. After developing the questionnaire, the template was created on Google Forms and disseminated in public on different social media channels (e.g., Telegram, WhatsApp, Facebook, email, etc.) by using a shareable link. Descriptive statistics were performed. Finally, multivariable logistic regression analysis was done to assess their relationship with socio-demographic factors. In total, 31.4% (n = 372) of respondents were willing to get a vaccine. One-third of respondents, 32.2% (n = 381), reported that COVID-19 vaccines are safe. Almost all 94.9% (n = 1124) responded that health workers should be vaccinated first. Only 21.7% (n = 257) willing to buy the vaccine if it is not provided free. Being female [OR (95% CI):1.85 (1.05-3.25)], aged less than 25 years old [OR (95% CI): 5.09 (3.41-7.59)], aged between 26-30 years [OR (95% CI): 3.57 (2.55-5.00)], being unmarried[OR (95% CI):1.12 (0.81-1.55)], urban in residence [OR (95% CI): 1.06 (0.69-1.62)], private sector worker in occupation [OR (95% CI):0.45 (0.26 -0.77)], university/college student [OR (95% CI): 0.88 (0.59-1.32)], not having a health-related job [OR (95% CI): 4.08 (2.57-6.48)], orthodox [OR (95% CI): 1.16 (0.61-2.19)], Muslim [OR (95% CI): 0.285 (0.13 -0.61)], educational status of university/above [OR (95% CI): 4.87 (3.15-7.53)] have a statistically significant association and were more likely willing to take COVID-19 than their counterparts. This study found that only 31.4% were willing to take the COVID-19 vaccine. Being female, older age, marital status, residence, occupations, not having a health-related job, religion, educational status were statistically significantly associated with willingness to receive the COVID-19 vaccine.